Successful endovascular coil embolization in an elder and asymptomatic case of anomalous systemic arterial supply to the normal basal segment. (2017) - Machida, Yuichiro; Motono, Nozomu; Matsui, Takuma; Usuda, Katsuo; Uramoto, Hidetaka
Highlights: An anomalous systemic arterial supply to the normal basal segment without sequestration is a rare congenital vascular malformation. We experienced a case of successful endovascular embolization of in an elderly and asymptomatic patient with an anomalous systemic arterial supply to the normal basal segment. Coil embolization is a very useful treatment method for elderly patients with an anomalous systemic arterial supply to the normal basal segment. Abstract: Introduction: An anomalous systemic arterial supply to the normal basal segment without sequestration is a rare congenital vascular malformation. The discovery age is relatively young, and the most common clinical symptom is hemoptysis due to pulmonary hypertension or heart failure. We herein describe a case of endovascular embolization of in an elderly and asymptomatic patient with an anomalous systemic arterial supply to the normal basal segment. Presentaition of case: An 80-year-old male was referred to our hospital due to an abnormal chest shadow. The patient was diagnosed with an anomalous systemic arterial supply to normal basal segment. We performed coil embolization via the catheterization. Discussion: The application of coil embolization via catheterization results in a low risk of infection and small burden on the body compared with surgery. There are few report of the coil embolization for an anomalous systemic arterial supply to the normal basal segment. Hence, it is necessary to accumulate additional cases. Conclusion: The outcome of thie case indicates that coil embolization is a very useful treatment method for elderly patients with an anomalous systemic arterial supply to the normal basal segment.